2020
DOI: 10.3390/min10030247
|View full text |Cite
|
Sign up to set email alerts
|

Metal Content of Stream Sediments as a Tool to Assess Remediation in an Area Recovering from Historic Mining Contamination

Abstract: Lead and zinc mining was booming in the early 1900s in and near Joplin, Missouri; a town within the Tri-State Mining District, USA. After the ore became depleted, mining companies moved out, leaving a profoundly disturbed land. Presently, over 90% of the land has been remediated. We collected sediment samples along two creeks flowing through the historically contaminated area that have been identified as major contributors of metals to downstream reservoirs, Center Creek (14 samples) and Turkey Creek (30 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The monitoring and rehabilitation studies have as a starting point the investigation of the quality of environmental factors affected by anthropogenic activities, such as: mining, metallurgical industry, machine building industry, intensive agriculture, etc. Even if some mines have been closed or abandoned, the surrounding areas remain a potential danger to fauna, flora, the aquatic environment and human health [1][2][3][4]. Different types of waste with varied metal content are stored either in specially designed landfills, which over time can produce discharges of toxic substances into the environment, or directly on the ground as long as the content of toxic substances is below certain limits imposed by laws [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring and rehabilitation studies have as a starting point the investigation of the quality of environmental factors affected by anthropogenic activities, such as: mining, metallurgical industry, machine building industry, intensive agriculture, etc. Even if some mines have been closed or abandoned, the surrounding areas remain a potential danger to fauna, flora, the aquatic environment and human health [1][2][3][4]. Different types of waste with varied metal content are stored either in specially designed landfills, which over time can produce discharges of toxic substances into the environment, or directly on the ground as long as the content of toxic substances is below certain limits imposed by laws [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…wastes were either spread-over [9] or used to fill mine cavities [10]. The former remediation method was applied to floodplain areas in Złoty Stok, a historical center of gold and arsenic mining in Poland.…”
mentioning
confidence: 99%
“…Another area where phytostabilization had been used to remediate a highly disturbed area of zinc and lead mines in southwest Missouri was analyzed for metal content and metal mobility by Gutiérrez et al [10]. Sediment samples collected from streams traversing this remediated area showed that toxic concentrations persist in the sediments.…”
mentioning
confidence: 99%
See 1 more Smart Citation